Articulate Storyline Learning Media with Gimkit Respiratory System Material to Improve Critical Thinking Skills - Cahyo Budhi Santoso; Irdalisa Irdalisa; Fetrimen; Somariah Fitriani (Universitas Pendidikan Ganesha, 2025)
Learning in elementary schools still shows low levels of students’ critical thinking skills due to the dominance of teacher-centered instruction and the suboptimal use of learning media. This condition causes students to rely on memorization and limits their ability to analyze and solve contextual problems. This study aims to analyze, design, and evaluate the development of interactive learning media using Articulate Storyline integrated with Gimkit to enhance the critical thinking skills of fifth-grade elementary school students. This research employed a research and development (R&D) approach using the ADDIE model. The research subjects included two expert validators (a media expert and a subject-matter expert) and 21 fifth-grade students as trial participants. Data were collected through critical thinking skills tests, student response questionnaires, expert validation sheets, and teacher practicality assessment sheets. Qualitative data were analyzed using content analysis techniques, while quantitative data were analyzed using descriptive statistics. The results indicate that the Articulate Storyline learning media integrated with Gimkit demonstrated very high validity based on evaluations by media and content experts and received positive responses from students. The developed media were proven to be feasible and effective in improving students’ critical thinking skills. Overall, this study concludes that the development of HOTS-oriented interactive learning media can serve as an innovative solution to enhance the quality of learning in elementary education. The implications of this study suggest that integrating interactive media and gamification can support more contextual, meaningful, and 21st-century skills–oriented learning.